2017
DOI: 10.5812/jogcr.11958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Ten-Week Aerobic Training on Atherogenic Indices, Lipid Profile, and Body Composition in Postmenopausal Women with Type II Diabetes

Abstract: Background: Atherogenic indices are among risk factors of diabetes which can cause cardiovascular diseases. The purpose of this study was to examine the effect of a 10-week aerobic training on atherogenic indices, lipid profile, and body composition in women with type II diabetes. Methods: In this quasi-experimental study, 40 postmenopausal women with type II diabetes (aged 40 to 60 years) were selected using convenience sampling method and were randomly assigned to experimental (n = 20) and control (n = 20) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Regarding the effect of exercise on atherogenic index in the previously mentioned subgroups, the results are in consistent with the study done by Antoninus et al [51] who showed that continuous exercise training significantly decrease the atherogenic index of plasma as a method of decreasing cardiovascular risk in sedentary non-obese males. On the other hands, Ghorbanian B et al [68] founded that aerobic exercise training induced non-significant decrease AIP in post-menopausal women, and TG, LDL-c/HDL-c, and TC/HDL-c significantly decreased .The current study also revealed elevated levels of platelets activations after ovariectomy is in agreement with the study done by Lundberg et al [69] and Singla A. et al [70] who reported that platelets of postmenopausal women were more reactive to aggregate than of premenopausal suggesting increased incidence of athero-thrombotic events in postmenopausal women. This may be because platelets contain the estrogen receptor β ,17β-estradiol has inhibitory effects on platelet aggregation in vitro and this inhibition is lost in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of exercise on atherogenic index in the previously mentioned subgroups, the results are in consistent with the study done by Antoninus et al [51] who showed that continuous exercise training significantly decrease the atherogenic index of plasma as a method of decreasing cardiovascular risk in sedentary non-obese males. On the other hands, Ghorbanian B et al [68] founded that aerobic exercise training induced non-significant decrease AIP in post-menopausal women, and TG, LDL-c/HDL-c, and TC/HDL-c significantly decreased .The current study also revealed elevated levels of platelets activations after ovariectomy is in agreement with the study done by Lundberg et al [69] and Singla A. et al [70] who reported that platelets of postmenopausal women were more reactive to aggregate than of premenopausal suggesting increased incidence of athero-thrombotic events in postmenopausal women. This may be because platelets contain the estrogen receptor β ,17β-estradiol has inhibitory effects on platelet aggregation in vitro and this inhibition is lost in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several human studies have also revealed the antidiabetic potential of sumac. In a study on the dietary supplementation with Rhus coriaria powder in type II diabetic women, significant reduction in serum glucose and insulin resistance index as well as the antioxidant potential of the diet were recorded [83]. The author also reported desirable effects on body weight, body mass index and other anthropometric indices.…”
Section: Antidiabetic Potential Of Sumacmentioning
confidence: 96%